2016
DOI: 10.1177/1550147716664235
|View full text |Cite
|
Sign up to set email alerts
|

Mobility-assisted big data collecting in wireless sensor networks

Abstract: In recent years, the big data emerged as a hot topic because of the rapid growth of the information and wireless communication technology. One of the significant sources of the big data is wireless sensor networks. Due to the power limitation of sensor nodes, energy-efficient big data collecting is a challenging task in wireless sensor networks. Being considered as an effective solution to address this challenge is to utilize sink's mobility to assist data collecting. Although this method can reduce the volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…This class of approaches aims to achieve lower data delivery latency. 16,[29][30][31][32][33]44 Sharma et al 29 suggested rendezvous-based routing protocols to resolve the energy consumption and latency requirements. Two different strategies are used for data transfer in the proposed approach.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…This class of approaches aims to achieve lower data delivery latency. 16,[29][30][31][32][33]44 Sharma et al 29 suggested rendezvous-based routing protocols to resolve the energy consumption and latency requirements. Two different strategies are used for data transfer in the proposed approach.…”
Section: Related Workmentioning
confidence: 99%
“…Mobility-assisted data collection is a crucial method for enhancing the efficiency of these networks. [15][16][17] Mobile data collector (MDC) can be viewed as remote nodes that minimize data delivery latency and communication costs and link the lower networks and higher cloud server on the IoT. 17,18 Data collection with mobile data collector can significantly increase the numerous performances of the networks, such as connectivity, reduces packet loss, and data delivery delay, and so forth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the proposed scheme, mobile collectors traverse a fixed path to collect data from cluster centroids and sensors in the clusters by multi-hop routing. Zhu et al [40] proposed a four-phase mobile data collecting protocol, called mobility-assisted big data collecting protocol (MDCP). MCDP operation is largely divided into network clustering, route planning, route combination, and data collecting.…”
Section: Technical Approaches To Wsn-based Big Data Systemsmentioning
confidence: 99%